Delivery of post-dental extraction care instructions with the aid of a novel educational kit: the UiTM dental students’ perspective / Nurkhalidah Sabrina Ikmalhisam … [et al.] - Ikmalhisam, Nurkhalidah Sabrina; Abdul Aziz, Nur Syakirah; Mah, Michelle Clare; Tengku Jamaluddin, Tengku Intan Baizura; Abdul Wahab, Hazmyr; Mohammad, Mohd Shawal Firdaus; Keng, Tan Su (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
The objective of this study is to assess Universiti Teknologi MARA (UiTM) dental students’ perspective on a novel patient educational kit in helping them to deliver post-dental extraction care instructions. All undergraduate clinical year dental students of the Faculty of Dentistry, UiTM were recruited for this cross-sectional study. 87.8% of these students have volunteered to participate in this study. An 8-minutes introductory video of the Post-Dental Extraction Care kit (PDEC-kit) was played when simultaneously showcasing the tools in the PDEC-kit to the participants. The participants then answered a set of validated self-administered questionnaires online on their perception and suggestions for improvement of the PDEC-kit, which comprises of 20 items that are rated by a 7-point Likert scale along with 7 open-ended questions. A total of 216 students participated voluntarily in this study. A vast majority of participants agreed that the PDEC-kit is useful (99.1%), easy to use (98.7%), and can improve patient’s understanding regarding post-dental extraction care instructions (99.1%). The information provided in the kit was also found to be appropriate for the patients (97.2%). Interestingly, students who had clinical experience in performing dental extractions have rated significantly higher scores for half of the questions (p<0.05). All but two participants (99.1%) thought that PDEC-kit would assist them in providing better post-dental extraction instructions to patients compared to providing verbal instructions only. Most of the participants (93.5%) also agreed that the kit can improve communication or rapport between patients and them. UiTM dental students agreed that PDEC-kit is beneficial and can help them in delivering more effective post-dental extraction care instructions to their patients.